2012
DOI: 10.1016/j.nicl.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in the brain of streptozotocin-induced type 1 diabetic rats revealed by diffusion tensor imaging

Abstract: Diabetes mellitus affects the brain. Both type 1 and type 2 diabetic patients are associated with white matter (WM) damage observable to diffusion tensor imaging (DTI). The underlying histopathological mechanisms, however, are poorly understood. The objectives of this study are 1) to determine whether streptozotocin (STZ)-induced type 1 diabetes is associated with WM damage observable to DTI; and 2) to understand the pathophysiological aspects underlying STZ-induced brain injuries. Male Sprague–Dawley rats rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 50 publications
7
33
3
Order By: Relevance
“…The histopathological changes in the brain in the diabetic rat group are in accordance with the study of Huang et al, who reported that diabetes reduced fatty acids in the striatum and motor/somatosensory cortex as early as 4 weeks after diabetes induction. Moreover, demyelination, axonal degradation, and neuronal dysfunction are observed in various brain regions, and these are associated with the inflammation and oxidative stress that affect hippocampal synaptic plasticity and apoptosis of neurons .…”
Section: Discussionsupporting
confidence: 89%
“…The histopathological changes in the brain in the diabetic rat group are in accordance with the study of Huang et al, who reported that diabetes reduced fatty acids in the striatum and motor/somatosensory cortex as early as 4 weeks after diabetes induction. Moreover, demyelination, axonal degradation, and neuronal dysfunction are observed in various brain regions, and these are associated with the inflammation and oxidative stress that affect hippocampal synaptic plasticity and apoptosis of neurons .…”
Section: Discussionsupporting
confidence: 89%
“…This appears to contradict previous studies reporting decreased bodyweight with advancing age in diabetics (14,15). However, in these latter studies, the follow-up period was significantly shorter.…”
Section: Rats With Streptozotocin-induced Diabetes Mellitus Display Acontrasting
confidence: 83%
“…The second phase, of severe hypoglycemia, was incriminated in the early deaths recorded following STZ administration. This hypothesis is further supported by the fact that administration of 5% dextrose efficiently prevented these early deaths (14). However, our results suggest that early free access to food may be just as effective in preventing early mortalities.…”
Section: Discussionsupporting
confidence: 73%
“…However, resveratrol was able to protect against akinesia development during the time course of the diabetes. This result demonstrates an unprecedented positive effect of resveratrol on this locomotor deficit, possibly due to its capability to attenuate some pathological mechanisms in brain regions responsible for motor control, such as the basal ganglia and cerebellum (Ates et al, 2007;Biessels et al, 1994;Cheema et al, 2011;Huang et al, 2012;Sima, 2010;Venturini et al, 2010).…”
Section: Discussionmentioning
confidence: 80%